Design of a Web-Based Village Asset Information System in Waimbidi Village - Lidjang, Antonius Kalujur; Rada, Yustina; Sitaniapessy, Desy Asnath (Institut Riset dan Publikasi Indonesia, 2024)
The village is one of the government agencies responsible for the process of managing village assets in an area. Waimbidi Village, Kambata Mapambuhang District, East Sumba Regency, currently managing village assets still uses manual methods by recording in master books, so that making reports takes a long time or even the required reports are incomplete. Recording using books can result in reports piling up, making it difficult to find data and taking a long time if one day it is needed. Based on these problems, a system is needed that can manage village assets. With the aim of being able to store village asset data permanently in a database. The system development method used in research is the waterfall method which starts from the process of planning, analysis, design and system implementation. The results of this research can create a Web-based Village Asset Information System in Villages, which can help the Waimbidi Village government manage asset data so that it can be more efficient and structured.